Extraovarian sex cord tumor with annular tubules discovered arising from a leiomyoma - William T. Jaegle; Erin A. Keyser; Lynn Messersmith; Robert O. Brady; Caela Miller (Elsevier, 2018)
Background: Sex cord tumors with annular tubules (SCTAT) are a rare (2%) subtype of ovarian sex cord-stromal tumor. SCTATs are usually cured at time of diagnosis by surgical resection with an oophorectomy. SCTATs have a 100%(disease related) five-year survival. One third of SCTAT tumors are associated with Peutz-Jeghers syndrome. Literature review discovered only two published cases of extra-ovarian SCTAT. Due to the rarity there is no standard treatment for extraovarian SCTATs. Case: A 39-year-old para-1 female with a symptomatic fibroid uterus, heavy menstrual bleeding, and a history of a uterine myomectomy, underwent an elective total abdominal hysterectomy. Intraoperative findings showed a 7.5 cm retroperitoneal mass adhered between the uterus and the right pelvic sidewall that on frozen section was found to be a degenerating leiomyoma. Final pathology demonstrated a 2 mm focus of incidental SCTAT adjacent to the serosal surface of the leiomyoma. The SCTAT was not associated with ectopic ovarian tissue or endometriosis. The patient's ovaries were normal on direct intraoperative examination, preoperative ultrasound and MRI. Six month postoperative surveillance ultrasound also demonstrated normal premenopausal ovaries. Conclusion: This is the first extraovarian SCTAT in the published literature arising from a leiomyoma. Our patient had no family history and displayed no syndromic features for Peutz-Jeghers Syndrome. Ultimately, she declined genetic testing. The lack of evidence of ovarian involvement on both imaging and on intraoperative examination made localization to either ovary impossible. The patient is currently being managed with surveillance since the morbidity associated with bilateral oophorectomy in the 4th decade of life exceeds the theoretical risk of SCTAT. Keywords: Extraovarian, Sex cord tumor with annular tubules, Peutz, Jeghers, Leiomyoma